2018
DOI: 10.3390/toxins10080332
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Novel Antiplatelet Peptide from Deinagkistrodon acutus Venom

Abstract: Animal venoms are considered as one of the most important sources for drug development. Deinagkistrodon acutus is famous for its toxicity to the human hematological system and envenomed patients develop a coagulation disorder with the symptoms of hemorrhage and microthrombi formation. The purpose of this study was to separate antiplatelet peptides from D. acutus venom using a combination of an ultrafiltration technique and reversed-phase high performance liquid chromatography (HPLC), which was guided by monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Snake venoms are a weapon library formed through millions of years of adaptive evolution for their prey and defense in the natural environment [40,41]. D. acutus is a poisonous snake, and its envenomation incurs hemorrhage and thrombus formation [42]. The venom contains an activator or inhibitor of the coagulation system, especially Kunitz/BPTI-type serine protease inhibitors [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Snake venoms are a weapon library formed through millions of years of adaptive evolution for their prey and defense in the natural environment [40,41]. D. acutus is a poisonous snake, and its envenomation incurs hemorrhage and thrombus formation [42]. The venom contains an activator or inhibitor of the coagulation system, especially Kunitz/BPTI-type serine protease inhibitors [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…By mimicking these biological entities such as viruses, exosomes, platelets, erythrocytes, and leukocytes, human endogenous cell-derived biomimetic drug carriers offer higher biosafety and targeting capabilities than artificial carriers (Parodi et al, 2017 ). Platelets play a key role in thrombosis (Kong et al, 2018 ). Natural platelets (PLT) can target adhesion to damaged vessels during thrombosis, so Li et al ( 2018 ) fabricated a biomimetic nanocarrier containing a PLT membrane envelope containing L-arginine and γ-Fe 2 O 3 magnetic nanoparticles (PAMN) for thrombus-targeted L-arginine delivery and in situ production of nitric oxide (NO; Figure 5A ).…”
Section: Nanomaterials-based Drug Deliverymentioning
confidence: 99%
“…Jin H and coworkers found that the most abundant constituent of the Deinagkistrodon acutus venom was phospholipases A2 (30.0%), snaclec (21.0%), antithrombin (17.8%), thrombin (8.1%) and metalloproteinases (4.2%) [8]. Deinagkistrodon acutus phospholipases A2 (dPLA2) that calcium ion dependent plays an essential role in the pathological process on the patient [7] [9]. Since this protease catalyzes the hydrolysis of the fatty acid ester at the sn-2 position of phospholipids releasing lysophospholipids and fatty acids [10] [11], and exerts a wide variety of relevant toxic actions such as myotoxic, neurotoxic, cardiotoxic, anticoagulant, cytotoxic, edematogenic, and proinflammatory effects [12] [13].…”
Section: Introductionmentioning
confidence: 99%